(untitled) (Web of Teachers: Inderscience Research, 2026)
This article analyzes the scientific significance of the methodology for developing students’ phonetic skills. The study examines the main components of phonetic competence, including the correct pronunciation of sounds, the normative use of word stress, the acquisition of intonation models, listening differentiation, and the formation of speech intelligibility. The theoretical and practical foundations of the development of phonetic skills are highlighted based on foreign experience and modern methodological approaches. According to the results of the study, the organization of phonetic classes in an integrated manner with segmental and suprasegmental units, auditory differentiation, communicative exercises, and digital technologies significantly increases the quality of students’ pronunciation and the effectiveness of oral speech. Statistical analysis showed that the results of the experimental group are higher than those of the control group. The article scientifically proves that the methodology for developing phonetic skills is an important component of the process of teaching a foreign language and provides conclusions on its improvement in the higher education system.